Dopuszczalność kary śmierci w ujęciu Tadeusza Ślipki. Kara śmierci rekapitulacją uprawnionej obrony - Krzysztof Butowski (Studia Ecologiae et Bioethicae)
The above article presents a critical analysis of a conception of limited admissibility of death penalty by Tadeusz Ślipko (restrained retention). Its essence is based on the fact that the victim of a wrongful aggressor has got the right to effectively defend his/her life. The source of such law lies in the absolute inviolability of innocent human’s life as a fundamental right of every man. In case of efficient act of aggression (cold – blooded murder), the state takes over the right to effectively defend the victim’s right of life by administering the perpetrator the death penalty (“life for life”).